IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH DALAM PENANGANAN SAMPAH RUMAH TANGGA DI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI TAHUN 2018-2019 - Ersi Ariesti; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Everyone has the right to a good and healthy living environment, as stated in Article 28 H paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The constitutional mandate provides a consequence that the government is obliged to provide public services in waste management. To get a good and healthy environment, the Kuantan Singingi Regency Government issued a Regent of Kuantan Singingi Regency Regulation on Kuantan Singingi Regency Policies an Strategies in Management of Household Waste and Household-like Waste Number 44 0f 2018. The target for handling household waste as referred to in Article 2 paragraph (1) letter (b) is 70% (seventy percent) of the total generated household waste.The purpose of this study was to determine the implementation of local government policies in handling household waste in Central Kuantan District which was carried out by the Environmental Agency of Kuantan Singingi Regency.In this study was to determine the implementation theory proposevd by George C.Edward III is known as the Direct and Indirect Impact on Implementation approach model. With the implementation process model consisting of four variables, namely communication, resources, disposition and bureaucratic structure. This study uses a research method with a qualitative research approach and type. This research was conducted in Central Kuantan District, Kuantan Singingi Regency. Data collection techniques by means of interviews and documentation.Based on the result of the study, it can be concluded that the waste management in Central Kuantan District has not been implemented optimally, the overall waste handling process requires active participation from all parties. So that the impact of waste accumulation that is too long does not create new problems for the environment. Keywords; Policy implementation, waste handling